Etiology of low vision and blindness in seven reference centers in Colombia between the years 2012 to 2017 - Suárez Escudero, Juan Camilo; Oviedo Cáceres, María del Pilar; Llano Naranjo, Yuliana; Arias Uribe, Johana; Villegas Mesa, José Daniel; Zapata Vásquez, María Camila; Ferreira Morales, Jorge Luis; Reyes Cisneros, Jessica Tatiana; Cano Calle, Karen; Goldfeder de Gracia, Sydney; González Franco, Juan Felipe; Astudillo Valverde, Esau (Revista Cuidarte, 2022)
Introduction: Low vision and blindness have high global prevalence, with categories of disability common in Colombia. Studies that characterize the etiology of permanent visual impairments are required. Objective: To identify and characterize the different causes of low vision and blindness in seven reference centers for the visually impaired population in Colombia, attended between 2012 and 2017 in six capital cities. Materials and methods: retrospective, case series, descriptive and multicenter study. Results: A sample of 879 records of visually impaired patients was available. Low vision is more prevalent for all age groups. 70% (612/879) low vision and 30% (267/879) blindness. The most common etiology in patients with low vision was age-related macular degeneration (DMAE) (24%, 144/612); in patients with blindness it was glaucoma (17%, 45/267). Discussion: Possibly in Colombia the causes of low vision and blindness go beyond cataracts, un corrected refractive errors and infectious blindness. Conclusions: The most common etiologies found are chronic and diverse eye conditions, which require specific interventions to decrease their prevalence and prevent cases of low vision and blindness. How to cite this article: Suárez Escudero Juan Camilo, Oviedo Cáceres María del Pilar, Llano Naranjo Yuliana, Arias Uribe Johana, Villegas Mesa José Daniel, Zapata Vásquez María Camila, Ferreira Morales Jorge Luis, Reyes Cisneros Jessica Tatiana, Cano Calle Karen, Goldfeder de Gracia Sydney, González Franco Juan Felipe, Astudillo Valverde Esau. Etiología de baja visión y ceguera en siete centros de referencia en Colombia entre los años 2012 a 2017. Revista Cuidarte. 2022;13(2):e2036. http://dx.doi.org/10.15649/cuidarte.2036